ANALISIS ELEMEN DALAM PENCIPTAAN KARAKTER DESAIN DI DALAM IP HYPNOSIS MIC - SEIYUU X RAPPER PROJECT - Ika Resmika Andelina (Narada : Jurnal Desain dan Seni, 2020)
Hypnosis Mic (Hypmic) is an IP developed by King Records, Japan. This is a collaborative project between hip-hop musicians and seiyuu (voice actors). They create 18 mic controller (MC) characters, which are voiceacted by the seiyuu. They perform songs created by rappers, and these songs are launched as music albums and music videos. These MCs are designed using 2D Japanese manga-anime style to attract potential listeners to the new hip-hop genre. There are many elements that contributed toHypmic IP making itfamous as it is now, especially in the character design. Because of the large number of characters that play a role in it, making the design of characters in different from one another becomes very important in order to be accepted by the audience.Mounsey mentioned holistic elements in creating a character that is loved, namely: the story behind the character, the nature of the character, audience and design of the character itself. Its expected that with this research will open up insights on the use of IP character designs with appropriate elements in order to become a reference in making IPs that are in accordance with the interests of the audience, to get more economic benefits in any field.